Production Afalan Analysis Using Value Stream Mapping (VSM) and Root Cause Analysis (RCA) Methods at PT. XYZ - Nando, Fiky Two; Anindya, Salsabila; Sarodin, Moc. Bah; Kennedy, John; Satya P, Akbar; Yusuf, Adam (Yayasan Cendekia Gagayunan Indonesia, 2025)
The competitiveness of the manufacturing industry demands companies to enhance production efficiency and reduce product defects. PT. Kerta Rajasa Raya, a woven bag manufacturing company, faces a high level of production scrap (defects), which decreases productivity and increases production costs. This study aims to analyze the defect rate, identify process waste using the Value Stream Mapping (VSM) approach, and determine the root causes of major defects through Root Cause Analysis (RCA). The research employs a descriptive case study method using secondary data from production and defect reports from January to June 2025. The results show that the total defect rate reached 3.44%, with the dominant defect being setting at 0.56% of total production. Based on the VSM mapping, the main wastes occur in the printing and cutting processes due to the absence of a standard operating procedure (SOP) for machine setting, long waiting times, and repeated rework. RCA analysis revealed that the root causes stem from insufficient operator training, machine wear, and variations in raw material quality. Improvement through the future state map, including the implementation of SOPs, kanban system, and operator training, led to a 52% improvement in process efficiency and a 50% reduction in defect rate. This study demonstrates that the integrated application of VSM and RCA is effective in identifying waste and improving production performance in manufacturing industries.